Cultural Branding in the Arab Region - Noha Mellor
The comparative study of cultural policies in the Arab region remains a relatively underexplored domain, particularly in how these policies influence nation branding and nation-building efforts. This exploratory study seeks to contribute to this nascent field by adopting a comparative lens to examine the cultural policies of three Arab nations: the United Arab Emirates (UAE), Saudi Arabia and Egypt. Through a document analysis of key policies from these countries, this research unveils the intricate ways cultural strategies are employed to articulate and disseminate national, ethical and political ideologies. The article articulates how each country$1 (Bs approach to cultural policy$1 (Bcommodification in the UAE, securitisation in Egypt and religionisation in Saudi Arabia$1 (Breflects and is shaped by unique local, regional and global power dynamics. By contextualising these policies within broader frameworks of market forces, security concerns and religious influences, the study offers insights into the complex interplay between cultural policymaking and nation branding in the Arab world.s